Analisis Spasial Prevalensi Kasus Demam Berdarah Dengue (Dbd) Di Wilayah Kerja Puskesmas Gambirsari - Hilaluddin, Aji Setiaji; , Sri Darnoto, SKM., MPH; , Miftahul Arozaq, S.Si (2015)
Dengue Hemorrhagic Fever (DHF) is a disease caused by dengue virus and is characterized by four clinical symptoms main high fever, manifestations of hemorrhage, hematomegali, and signs of circulatory failure until the onset of shock (syndrome of shock dengue) as a result of leakage of plasma can cause death. This research is descriptive analytic Geographic Information System. The population in this study, all cases of dengue hemorrhagic fever (DHF) in the working areaI Puskesmas Gambirsari. The population in this study as many as 103 people. The prevalence of cases of dengue hemorrhagic fever in Public Health of Gambirsari is 0,18. The results in this study is a map of the distribution of cases, as well as the buffering of cases of dengue hemorrhagic fever (DHF) working area Puskesmas Gambirsari.